Hubungan antara Kebiasaan Latihan Yoga terhadap Kualitas Tidur pada Komunitas Lansia Widya Werda Sentana Santi - Kadek Dwitya Widi Adnyani Dwitya; Luh Gede Pradnyawati; Anny Eka Pratiwi (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2023)
The complaint that is often experienced by the elderly is a decrease in sleep quality which has an impact on reducing welfare and productivity in the life of the elderly. Various efforts have been made to overcome the problem of decreasing sleep quality in the elderly, one of which is by practicing yoga. The preliminary survey found that there were differences in sleep quality between the elderly who regularly practiced yoga and those who did not practice yoga regularly. This study aims to determine the relationship between yoga practice habits and sleep quality in the elderly community of Widya Werda Sentana Santi. This research is descriptive research with a cross-sectional research design. The number of samples in this study was 50 elderly people from the Widya Werda Sentana Santi Community in Banjar Nyuh Kuning, Ubud District, Gianyar Regency who met the criteria. The time of research was carried out from July - September 2022. Data was obtained through primary data, namely the PSQI questionnaire and observation sheets. Data were analyzed univariately and bivariate using Statistical Product and Service Solutions (SPSS). The results of the univariate analysis showed that 84% of the elderly in the community practiced yoga actively and 8% passively. The results of the analysis on the bivariate test showed that there was a significant relationship between the length of time the elderly joined the community (p-value <0.05; 95% CI = 1.35-5.75), the duration of yoga practice (p-value <0.05; 95 % CI = 1.35-5.28), amount of yoga practice (p-value < 0.05; 95% CI = 1.36-4.98), and type of yoga practice (p-value < 0.05; 95% CI = 2.14-27.49) which was carried out on the sleep quality of the elderly. The elderly community is expected to optimize yoga practice as a form of effort to improve the health of the elderly and as a preventive measure to prevent disturbances in bodily functions.